Analisis Net Profit Margin (NPM) Dan Current Ratio (CR) Terhadap Dividend Payout Ratio (DPR) (Studi Kasus pada Perusahaan Sektor Infrastruktur yang Terdaftar di BEI pada Tahun 2015-2019) - Fajjar Mustofa; Ronny Malavia Mardani; Ety Saraswati (UNIVERSITAS ISLAM MALANG, 2021)
AbstractThe purpose of this study to determine how the impact of Net Profit Margin (NPM) and Current Ratio (CR) to the Dividend Payout Ratio (DPR) of infrastructure companies registered on the IDX in 2015-2019. The independent variable is the Net Profit Margin (NPM) and the Current Ratio (CR), while the dependent variable in this study is the Dividend Payout Ratio (DPR). The population in this study were 52 companies in the infrastructure sector registered on the IDX in 2015-2019 and the research sample was determined using purposive sampling technique, namely selecting samples based on certain criteria so that a sample of 13 companies was obtained. The documentation method is used as a method of collecting company annual report data which is downloaded from the IDX website and companies. Multiple linear regression is the analytical techniques used in this study. From the results of data analysis, it is concluded that the Net Profit Margin (NPM) has a positive but insignificant impact to the Dividend Payout Ratio (DPR. Meanwhile, the Current Ratio (CR) has a positive and significant impact to the Dividen Payout Ratio (DPR). Keywords: Net Profit Margin (NPM), Current Ratio (CR), Dividend Payout Ratio (DPR).